Musculoskeletal Disorders of the Cervical Spine Following Neck Dissections Due to Malignancies of the Head And Neck (International Journal of Scientific Research and Management (IJSRM), 2019)
Neck dissections are surgical interventions aiming the removal of lymph nodes from specific areas of the neck, together with non-lymphatic structures falling within the scope of the operation – m. sternocleidomasstoideus (MSCM), v. jugularis interna (VJI), n. accessorius (N.XI). Due to the involvement of important anatomical structures in the neck dissections, postoperative outcoomes and complications associated with impaired function of the musculoskeletal system of the neck arise. The purpose of the present study is to determine the degree of cervical spine movements depending on the volume of surgical neck dissection. Methods. The goniometry method was used to evaluate the motor function of the operated patients. The results obtained were analyzed via SPSS Vers23.0. Results. A statistically significant difference was observed postoperatively at the 3rd month in all directions of movement studied in the three groups of operative interventions (neck dissections): flexion – F(2,65)=643.566, p<0.001; extension – F(2,65)=445.045, p<0.001; lateral flexion – F(2,65)=314.077, p<0.001; rotation – F(2,65)=121.980, p<0.001. Conclusion. Assessment of the cervical spine shows that all directions of movement are affected, most significantly affecting lateral flexion in all groups of operated patients with neck dissection.